The public was exposed to cultural programs in the Iraqi satellite channels and the achieved publications - Al-Essa, Mohammed R. Kadhim; mahmood, Median Umran (International Journal of Psychosocial Rehabilitation, 2020)
The research dealt with the Iraqi public’s use of cultural TV programs through Iraqi satellite channels as media means of communication that have their advantages and characteristics that make them capable of spreading culture and cultural heritage, where the current research problem lies in a major question that is “What are the fulfills achieved by the public from their exposure to cultural programs in satellite TV? Iraqi ", as the research aims to determine the patterns of exposure and the extent of public follow-up to these cultural programs and the motives for viewing, and to identify the gratifications achieved by the public from watching cultural programs in Iraqi satellite channels, and this research is descriptive in terms of type, where the researchers adopted the survey method, for the purpose of reaching To the required results, the sample was chosen according to the intentional sample method for the viewers of cultural programs in Iraqi satellite channels. The size of the sample was (400) single adults (more than 18 years), and the research concluded a set of results as follows: 1- The results of the research revealed the irregularity of the respondents in watching cultural programs through Iraqi satellite channels, as they became increasingly preoccupied with daily life matters, which made them exposed to less than half an hour a day and in the evening broadcast period, which is a period of rest and relaxation for the Iraqi public, so poetry and literature were among the most programs The cultural sample members would like to see during that period. 2- The results of the research indicated that the motives for watching the sample members of the cultural programs in Iraqi satellite channels are to satisfy their cultural interests, and this is clear from the fact that most of the sample members are from the educated class with a university educational level and have diverse cultural interests. 3- The gratifications achieved by watching cultural programs through Iraqi satellite channels are always identifying views on the cultural issues raised and sometimes identifying prominent cultural figures, always listening to poetry and literature presented, and interacting with cultural programs sometimes, which viewers always feel enjoyment and happiness, and listening to music and songs And know the latest developments in cultural events.